Floristic heterogeneity between forested sites in Kibale National Park, Uganda: insights into the fine-scale determinants of density in a large-bodied frugivorous primate - Potts, Kevin B.; Chapman, Colin A.; Lwanga, Jeremiah S. (Journal of animal ecology, 2009)
Factors regulating the density of consumer populations include both top-down (predation effects and disease) and bottom-up (resource availability and quality) components. Although the relative influence of each component is widely debated (e.g. Polis & Strong 1996; Schmitz, Hambäck & Beckerman 2000; Terborgh et al. 2001), it is likely that top-down and bottom-up processes play synergistic roles in limiting consumers (Krebs et al. 1995). Disentangling the relative effects of predators vs. resources ultimately requires either eliminating or controlling for one of these variables, thereby assessing the impact of the other (Moen & Oksanen 1998). Similarly, bottom-up and top-down regulatory factors may exert both spatial and temporal influences on consumers, and a complete understanding of how the environment limits populations requires examination of both factors. For example, Brown, Mehlman & Stevens (1995) found that the spatial distribution of abundance within North American bird species was well explained by concomitant spatial environmental variability that was relatively fixed over time. However, Ives & Klopfer (1997), building on Brown et al.’s (1995) work, suggested that similar spatial patterning could be created from temporal environmental variation without a fixed spatial component. Tropical forests are ideal sites in which to simultaneously incorporate both spatial and temporal components in understanding the determinants of density in vertebrates, particularly frugivorous species, as such ecosystems generally exhibit considerable spatiotemporal variability in fruiting phenology (van Schaik, Terborgh & Wright 1993; Condit et al. 2002; Cannon et al. 2007). Furthermore, the great apes (family Hominidae), the vast majority of which inhabit tropical forests (Campbell et al. 2007), represent a model taxon in which to address the role of bottom-up processes in regulating vertebrate frugivores. With some exceptions, most great apes are not subject to notable mortality risk from natural predators (Miller & Treves 2007), thus removing (or at least diminishing) the effect of top-down processes. We assessed which fine-scale ecological characteristics are potentially limiting the density of chimpanzees (Pan troglodytes Blumenbach, 1799) by comparing the spatiotemporal availability of resources between the home ranges of two communities of known size inhabiting Kibale National Park (KNP), Uganda. Chimpanzees are large-bodied, wide-ranging frugivorous apes with home ranges of c. 8–40 km2. The two communities included in this study are separated by only 12 km (or approximately one to three home ranges), and that at Ngogo (hereafter referred to as the ‘high-chimpanzee-density’ site) is the largest and most densely populated chimpanzee community currently known, with over 155 members (5·1 individuals km−2; Mitani & Watts 2005; Potts 2008), compared to c. 50 chimpanzees (1·5 individuals km−2) at Kanyawara (hereafter referred to as the ‘low-chimpanzee-density’ site; Muller & Wrangham 2004). Detailed long-term observations from this population suggest that other extrinsic variables (both top-down and bottom-up factors) not explicitly dealt with here, including disease, inter-specific niche overlap, predation, and/or non-fruit resource availability have played relatively limited roles in influencing spatial variations in chimpanzee density in KNP (Potts 2008). This population therefore presents an ideal model for isolating the effects of fruit resource availability in both space and time on the population ecology of large-bodied tropical frugivores.
Keywords: animal density, chimpanzee, food availability, population regulation.